Pengaruh Religiusitas, Love of Money, dan Status Sosial Ekonomi Terhadap Kecenderungan Perilaku Tax Evasion dalam Perspektif Ekonomi Islam - Riska Oktaviana; M Iqbal Fasa; Suharto Suharto (Jurnal Ekonomi Dan Statistik Indonesia, 2021)
Tax is a mandatory expenditure imposed on taxpayers to assist the development of the country. However, taxpayers feel that taxes are a burden for them, because the distribution of development has not been maximized, causing the people to feel reluctant to pay their obligations. So in this case the taxpayer is trying to find a way to evade taxes. The purpose of this study was to determine the effect of religiosity, love of money, and socio-economic status on the tendency of tax evasion behavior in an Islamic economic perspective. This study used a literature study which refers to journals and books. The results of this study reveal that religiosity and love of money have an effect on tax evasion behavior. However, socioeconomic status has no effect on tax evasion behavior.